1985
DOI: 10.1093/infdis/152.6.1275
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis: Its Role in Tubal Infertility

Abstract: We compared the prevalence of antibody to Chlamydia trachomatis among 88 women undergoing an evaluation for infertility and 49 women attending an antenatal clinic. Demographic data regarding sexual behavior were also collected. Eighteen women had tubal infertility and 70 had infertility due to a variety of other reasons. In comparison with women who had other causes for infertility, women with tubal infertility began coitus sooner (17.7 +/- 2.2 years vs. 19.5 +/- 3.4 years, P less than .05) and had more lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(113 citation statements)
references
References 18 publications
6
105
1
1
Order By: Relevance
“…Further, the cysteine-rich nature of this protein and its expression late in the developmental cycle suggest involvement in the disul- fide-mediated changes that are essential for the switch between intracellular and extracellular stages of this organism (4,9). The antigenic significance of this protein in the host immune response is demonstrated by studies in which the presence of antibodies to OMP2 is consistently observed in active infection (5,8,21) and is correlated with disease status (5,6,11). Although no differences in antigenicity have been observed between the OMP2s of trachoma and LGV biovars (3,20), significant differences in physical (20) and chemical (3) properties of this protein between biovars have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the cysteine-rich nature of this protein and its expression late in the developmental cycle suggest involvement in the disul- fide-mediated changes that are essential for the switch between intracellular and extracellular stages of this organism (4,9). The antigenic significance of this protein in the host immune response is demonstrated by studies in which the presence of antibodies to OMP2 is consistently observed in active infection (5,8,21) and is correlated with disease status (5,6,11). Although no differences in antigenicity have been observed between the OMP2s of trachoma and LGV biovars (3,20), significant differences in physical (20) and chemical (3) properties of this protein between biovars have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Repeated or persistent infection appears to underlay much of the tissue-damaging effects of infection and can lead to infertility and blindness (1)(2)(3)(4). Because of the public health importance of chlamydial diseases, there has been long-standing interest in developing an effective vaccine (5-7).…”
Section: Gm-csf Transgene-based Adjuvant Allows the Establishment Of mentioning
confidence: 99%
“…Chlamydia infection begins in the lower genital tracts; however, the diseases induced by chlamydia such as pelvic inflammatory disease (PID), infertility, and ectopic pregnancy take place in the fallopian tubes in the upper genital tracts [2,45,46]. Therefore, chlamydia must overcome host immunity, particularly in the genital mucosa that controls the spread and ascension of chlamydia.…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia trachomatis (C. trachomatis) infection in the lower genital tract (LGT) of women can lead to inflammatory pathologies such as hydrosalpinx in the upper genital tract (UGT), resulting in severe complications, including ectopic pregnancy and infertility [1][2][3]. More than 1.4 million cases of chlamydial infection are reported to the Centers for Disease Control and Prevention (CDC) in the United States annually [4], but the actual number of C. trachomatis infections is likely to be significantly higher since many infections are asymptomatic and remain undiagnosed.…”
Section: Introductionmentioning
confidence: 99%